The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1590/es.251642
|View full text |Cite
|
Sign up to set email alerts
|

Los Grupos De Whatsapp Y La Construcción De Nuevas Ciudadanías en Las Escuelas

Abstract: RESUMEN Este artículo aborda los debates sobre las nuevas formas de ciudadanía que emergen con las redes sociales en el espacio educativo, que tienden a horizontalizar los discursos dentro de una organización jerárquica. A partir del análisis de la observación de dos grupos de WhatsApp de docentes en escuelas primarias de Ciudad de México y de entrevistas, se indaga cómo se organiza la participación de los docentes en estos nuevos espacios, prestando atención a los lenguajes, texturas y bordes, y a las interpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Making a link between media literacy and the concept of empowerment raises the issue of the role of men's and women's involvement and participation in the digital environment. In academic works, different studies (Tufecki, 2017;Dussel et al, 2021) discuss the contradictions of the new conditions of popular participation in the digital world. While some authors observe that more gender differences have been found in the offline world, in the "real" life of young people (Renau et al, 2012), others continue to focus on the risks presented by beauty standards and the persistence of stereotypical female roles (Fernández-de-Arroyabe-Olaortua et al, 2018;Santos et al, 2022) and stereotypical gender roles in general (Ringrose et al, 2013;Van Oosten et al, 2017).…”
Section: Gender Perspective and Transmedia Educationmentioning
confidence: 99%
“…Making a link between media literacy and the concept of empowerment raises the issue of the role of men's and women's involvement and participation in the digital environment. In academic works, different studies (Tufecki, 2017;Dussel et al, 2021) discuss the contradictions of the new conditions of popular participation in the digital world. While some authors observe that more gender differences have been found in the offline world, in the "real" life of young people (Renau et al, 2012), others continue to focus on the risks presented by beauty standards and the persistence of stereotypical female roles (Fernández-de-Arroyabe-Olaortua et al, 2018;Santos et al, 2022) and stereotypical gender roles in general (Ringrose et al, 2013;Van Oosten et al, 2017).…”
Section: Gender Perspective and Transmedia Educationmentioning
confidence: 99%
“…Todos los participantes relataron cómo, durante la pandemia, transitaron por dificultades e incertidumbres en sus prácticas pedagógicas. Describieron un arco que iba desde el uso de herramientas digitales acotadas y conocidas por ellos hasta la incorporación de una gran variedad de recursos dirigidos, principalmente, a capturar la evanescente atención de sus estudiantes, una preocupación previa a la pandemia que se incrementó con la escolarización remota (Dussel & Cardona, 2021). Tendieron a enfrentar el primer periodo del semestre enviando guías de actividades, pero pronto la necesidad de motivar a los estudiantes los hizo explorar e incorporar nuevas herramientas y plataformas, buscando entregar contenidos visualmente "atractivos".…”
Section: Adaptación a La Enseñanza Remota En Pandemiaunclassified
“…(Dussel & Cardona, 2021).La pandemia llegó a Chile pocos meses después del estallido social que en octubre de 2019 iniciaron estudiantes de secundaria, exigiendo al Estado mayor seguridad y justicia social(Rojas Fabris, 2020). Su llegada coincidió con el inicio del año escolar y, tras solo dos semanas de clases presenciales, se ordenó el cierre de las escuelas, situación que empezó a revertirse hacia finales de 2020 en los sectores de mayores ingresos(Bellei et al, 2022).En Chile, la pandemia se acopló a un sistema educativo centralizado y mercantilizado que ha sido asociado a segregación socioeconómica y al debilitamiento de la educación pública (AlarcónLópez & Falabella, 2021;Bellei et al, 2018) 1 .…”
unclassified
“…A 2019 survey indicated that 65% of the school students in Brazil who used the Internet had an Instagram profile, 85% had a WhatsApp account, and of these, 61% used WhatsApp for school work (CETIC 2019, cited in Gonsales andAmiel 2020: 4). Teachers in Mexico and Argentina communicate intensively in WhatsApp group chats, with new 'popular' leaders emerging through their authority in a specific kind of chat which emphasises socio-emotional well-being (Dussel and Fuentes Cardona 2021). Over the past 15 years, several national one-to-one initiatives have distributed tablets or computers to students, e.g.…”
Section: Practices Appropriations Social Relationsmentioning
confidence: 99%